The Spectrum and Impact of Metabolic Dysfunction in MAFLD: A Longitudinal Cohort Analysis of 32,683 Overweight and Obese Individuals - Chan, Kai En; Ng, Cheng Han; Fu, Clarissa Elysia; Quek, Jingxuan; Kong, Gwyneth; Goh, Yi Jie; Zeng, Rebecca Wenling; Tseng, Michael; Aggarwal, Manik; Nah, Benjamin; Chee, Douglas; Wong, Zhen Yu; et al. (Clinical gastroenterology and hepatology, 2023)
Metabolic associated fatty liver disease (MAFLD) was recently proposed as an alternative name change for better encapsulation of disease. However, there exists a spectrum of MAFLD where both metabolically healthy (MH) and metabolically unhealthy (MU) individuals are included. In view of limited evidence, we sought to examine the prevalence, clinical characteristics, and differences in outcomes of MH-MAFLD at the population level. Data were used from the United States National Health and Nutrition Examination Survey 1999 to 2018. Multivariate logistic regression analysis was used to obtain odds ratios for the estimation of events. Survival analysis was conducted with Cox regression and the Fine-Gray subdistribution model. There were 32,683 overweight and obese individuals included in the analysis. In MAFLD patients, the prevalence of MH-MAFLD was 6.92% (95% confidence interval [CI], 6.58%–7.27%), and 93.08% (95% CI, 92.73%–93.42%) were considered as MU-MAFLD. Multivariate analysis found a significantly higher risk of MACE (odds ratio, 1.38; 95% CI, 1.28–1.49; P < .01), all-cause (hazard ratio, 1.24; 95% CI, 1.17–1.32; P < .01), cardiovascular disease (SHR, 1.20; 95% CI, 1.02–1.42; P = .03), and cancer mortality (SHR, 1.24; 95% CI, 1.07–1.44; P < .01) in MU-MAFLD relative to non-MAFLD. However, MH-MAFLD individuals were not associated with a statistically significant increased risk of these adverse outcomes compared with non-MAFLD. MU-MAFLD diabetics were also at a higher risk of adverse events compared with non-diabetics. This study reports on the heterogeneity and spectrum of metabolic dysfunction that exists in overweight and obese MAFLD. Although MAFLD may potentially be advantageous in improving awareness and patient outcomes, there remains substantial heterogeneity within patients included in MAFLD on the basis of the underlying metabolic burden.